RETIREMENT BENEFIT PROCESSING OF THE NEW PENSION SCHEME AND ITS IMPLICATIONS ON PUBLIC SERVICE RETIREES’ WELFARISM IN SOUTH WEST NIGERIA - Dauda Ayodele MORAKINYO; Roseline Moyosore OJOKUKU; Johnson Olusola LAOSEBIKAN; Nureni Adekunle LAWAL; Lawal Ayofe BAKARE (Business Excellence and Management)
The study analysed the retirement benefit processing of the new pension scheme and its implications the welfare of public service retirees’ welfarism in selected States of Southwest Nigeria. Descriptive survey design was adopted with primary data as the major source of data. The study population comprised eighteen thousand nine hundred and ten (18,910) pensioners in the South west Nigeria as documented by the Nigeria Bureau of Statistics. Multi staged sampling technique was adopted to select 10% of the study population from each of the three states of Osun, Ondo, and Ogun in Southwest Nigeria totaling one thousand eight hundred and ninety one (1,891) as sample size. The data were collected with the aid of structured questionnaire and interview schedule. Both descriptive and inferential statistics were utilized to analyse the data with the aid of SPSS. Findings revealed that retirement documentation process implementation account has a significant positive effect on the welfare among the pensioners as evidenced by R2 = 0.358, F =170.941, and p<0.000. It was also found that retirement documentation process account for about 32% of changes in welfarism among the pensioners in the Southwest Nigeria. The study thus argued that the processing of retirement benefit contributes significantly to the low welfarism of public service retirees in selected states of Southwest Nigeria.